Bradykinin Impairs and HOE 140 does not Protect Rat Hindlimb Skeletal Muscle Against Tourniquet-induced Reperfusion Injury. (2nd January 2016) - Mendonça, Luciano R.; Joviliano, Edwaldo E.; Ramalho, Fernando S.; Ramalho, Leandra N Z.; Evora, Paulo R. B.; Piccinato, Carlos E.
ABSTRACT: Background: Bradykinin (BK) is used in different tissues. Dose-dependent studies have demonstrated that low doses protect against ischemia/reperfusion (I/R) injury while higher doses lead to adverse effects. Although the beneficial effects of BK infusion were observed in myocardium, its role on the I/R impact in skeletal muscle (SM) has not been fully clarified. Objective: This study was carried out to evaluate the effects of BK, administered in the hindlimbs of rats subjected to I/R. Methods: The study design included three experimental groups: Group 1 control (saline), Group 2 (bradykinin), and Group 3 (HOE 140, a BK2 receptor blocker). In all three groups, rats were subjected to hindlimb ischemia for a total of 2 h followed by continuous 4 h of reperfusion with pharmacological interventions. The methods include analysis of enzymes (lactate dehydrogenase—LDH and creatinine phosphokinase—CPK), cell membrane marker of injury (malondialdeyde—MDA), recruitment of neutrophils (myeloperoxidase—MPO), and apoptosis index (immunohistochemistry TUNEL in situ peroxidase dead end). Results: Except for the apoptotic index, all parameters studied were shown to be elevated in the reperfusion group intervened with BK. The blocking of BK2 receptors by HOE 140 did not affect the I/R injury. Conclusion: After 2 h of total ischemia, infusion of bradykinin during 4 h of reperfusion, worsened the I/R injury in the hindlimb skeletal muscle.